Determinant Analysis of the Effectiveness of Accounting Information Systems - Ni Putu Lisa Ernawatiningsih; Putu Kepramareni (Journal of International Conference Proceedings (JICP), 2019)
Accounting Information Systems are defined as computer-based systems that process financial information and support the task of decision making in the context of coordination and control of organizational activities. The purpose of this study is to obtain empirical evidence about the effect of incentives, level of education, experience, and skills on the effectiveness of accounting information systems at PT. Angkasa Pura Logistik. The sampling technique used in this study is a non probability sampling technique with a purposive sampling method. While the data analysis technique used in this study is multiple linear regression analysis. The results of the analysis show that incentives, levels of education, experience, and skills have a positive effect on improving accounting information systems at PT. Angkasa Pura Logistik.